A furan-2-carbonyl C-glucoside and an alkyl glucoside from the parasitic plant, Dendrophthoe pentandra. (September 2017) - Sahakitpichan, Poolsak; Disadee, Wannaporn; Buntawong, Rada; Chimnoi, Nitirat; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: Furan-2-carbonyl C -(6′- O -galloyl)-β-glucopyranoside (scleropentaside F) and butane-2, 3-diol 2- O -(6′- O -galloyl)-β-glucopyranoside were isolated from Dendrophthoe pentandra . Highlights: A new furan-2-carbonyl C -(6′- O -galloyl)-β-glucoside was isolated from Dendrophthoe pentandra . A new alkyl glucoside was isolated from Dendrophthoe pentandra. . The results from this plant might be useful for chemotaxonomic studies of the order Santalales. Abstract: A new furan-2-carbonyl C -(6′- O -galloyl)-β-glucopyranoside (scleropentaside F, 1 ) and a new alkyl glucoside [butane-2, 3-diol 2-(6′- O -galloyl)- O -β-glucopyranoside, 2 ] were isolated from the entire hemi-parasitic plant, Dendrophthoe pentandra growing on Tectona grandis together with ten known compounds including, benzyl- O -β-d -glucopyranoside (3 ), benzyl- O -α-l -rhamnopyranosyl-(1 → 6)-β-d -glucopyranoside (4 ), benzyl- O -β-d -apiofuranosyl-(1 → 6)-β-d -glucopyranoside (5 ), methyl gallate 3- O -β-d -glucopyranoside (6 ), methyl gallate 3- O -(6′- O -galloyl)-β-d -glucopyranoside (7 ), (+)-catechin (8 ), procyanidin B-1 (9 ) and procyanidin B-3 (10 ), bridelionoside A (11 ), and kiwiionoside (12 ). In addition, compounds1, 3 –9 were isolated from this species growing on the different host, Mangifera indica . The structure elucidations were based on physical data and spectroscopic evidence including 1D and 2D experiments.